Synthesis and Characterization of TiO2 Semiconductor Doped by AgNO3 and Their Application as Photoanode in Dye-sensitized Solar Cells - Marjoni Imamora Ali Umar; Nanda Faizil; Akrajas Ali Umar; Siti Khatijah Md Saad (Universitas Pendidikan Mandalika, 2020)
The use of Titanium dioxide (TiO2) semiconductors in Dye-Sensitized Solar Cells (DSSC) devices have been extensively studied and synthesized with various techniques to obtain optimal performance. The TiO2 semiconductors with optimal performance are influenced by the growth method, the time of growth, the shape of the microstructure, and the optical properties. In this study, it was reported about the effect of silver nanoparticles (AgNO3) doping onto TiO2 semiconductors on their microstructure, reflectance, and efficiency of the DSSC device. The synthesis of TiO2 was carried out using liquid phase deposition (LPD) and immersed into an AgNO3 solution with a variation of time namely 0.5 h, 1 h, 2 h, 4 h, and 6 h. The entire TiO2 + AgNO3 sample, then used as a photoanode on DSSC with plastisol as a counter electrode. Characterization of microstructure, reflectance, and DSSC performance was carried out by using field emission scanning electron microscopy (FESEM), Uv-Vis Spectrophotometer, and Gamry Instrument, respectively. The FESEM results show that AgNO3 has successfully grown on the ITO substrate in a spherical shape with an average particle diameter ranging from 1.52-2.29 μm. From observations using the Uv-Vis Spectrophotometer, obtained the energy band gap values ranged from 0.22 to 2.27 eV. The best results of DSSC device efficiency, with TiO2+AgNO3/Dye/Plastisol structure, have resulted in the Voc of 0.694 V, current density (Jsc) of 0,943 mA/cm2and fill factor (FF) of 43,50% which is obtained at sample 1.